Primary Report of Totally Tubeless Percutaneous Nephrolithotomy Despite Pelvi-calyceal Perforations - Aghamir, Seyed Mohammad Kazem; Salavati, Alborz; Hamidi, Morteza; FallahNejad, Asghar (Urology Journal, 2017)
Purpose: Nephrostomy tube insertion and/or a ureteral stent placement is advised when pelvi-calyceal perforations are encountered during percutaneous nephrolithotomy (PNL) nevertheless totally tubeless PNL is a possible exit strategy in percutaneous renal surgery therefore case series on the short term clinical outcomes of noninvasive management of iatrogenic pelvicalyceal perforations encountered during PNL is presented. Patients and Methods: During retrospective analysis of 1271 PNL procedures, 25 incidents of accidental ureteral catheter/ jj stent dislodgement during first 24 post-operative hours were identified in patient who had pelvi calyceal perforations and had no nephrostomy tube (tubeless). Thirteen patients could not be re-stented nor a nephrostomy tube could have been placed for them mainly due to patient refusal or comorbid conditions. The main outcome was rate of successful noninvasive management. Results: Eighteen Patients bearing mucosal tears (grade I trauma) or visible peri-pelvic fat (grade II) successfully recovered without need for ureteral stenting or nephrostomy (72.0%). In seven (28.0%) cases of extension of the perforation into the peri-pelvic fat (grade III), either nephrostomy insertion or JJ stenting was needed for resolution of fever and urinoma. The major limitation was the necessity to exclude patients and manage them in the standard fashion according to clinical guidelines. Conclusion: Iatrogenic perforations of the collecting system are quite diverse in terms of severity that result in different natural histories and not all might need urinary diversion via nephrostomy or ureteral stenting. Low grade perforations may be successfully managed in totally tubeless fashion nevertheless further prospective investigations seem warranted.